Intelligibility & the Limits of Ontology: Pluralism, Monism, & Finitude - (:unkn) unknown (My University, 2024)
The ontological pluralist commits to a generic concept of being by claiming everything exists in one way or another. This generic concept of being includes all entities: entities existing in one way and entities existing in another. In this essay, I develop a generic concept of being using Kris McDaniel’s pluralism as a foundation. I argue that the generic concept of being is intimately linked to thought. I use my generic concept of being to respond to an objection concerning fundamentality and the principle of purity, which results in rejecting the latter. Second, I argue that McDaniel’s pluralism is inconsistent because differentiating the many ways of being relies on us. Thus, I conclude that being only appears to fragment because of us, and pluralism cannot hold for fundamental reality.
Keywords: Finitude; Intelligibility; Metaphysics; Ontology; Pluralism